Butyric acid: what is the future for this old substance? (Swiss Medical Weekly, 2012)
In this brief review, we present some data from the literature on butyric acid and some of its more interesting potential uses, especially in the field of gastroenterology. Due to its principal characteristics, butyric acid is primarily used for pathologies of the colon (functional, inflammatory). Although only preliminary data are available, butyric acid may also have interesting extraintestinal applications, such as in the treatment of haematological, metabolic, and neurological pathologies.